Thromboembolism in the Complications of Long COVID-19 - Lopes, Leilani A; Agrawal, Devendra K (Cardiology and Cardiovascular Medicine, 2023)
SARS-CoV-2 is a +ssRNA helical coronavirus responsible for the global pandemic caused by coronavirus disease 19 (COVID-19). Classical clinical symptoms from primary COVID-19 when symptomatic include cough, fever, pneumonia or even ARDS; however, they are limited primarily to the respiratory system. Long-COVID-19 sequalae is responsible for many pathologies in almost every organ system and may be present in up to 30% of patients who have developed COVID-19. Our review focuses on how long-COVID-19 (3 -24 weeks after primary symptoms) may lead to an increased risk for stroke and thromboembolism. Patients who were found to be primarily at risk for thrombotic events included critically ill and immunocompromised patients. Additional risk factors for thromboembolism and stroke included diabetes, hypertension, respiratory and cardiovascular disease, and obesity. The etiology of how long-COVID-19 leads to a hypercoagulable state are yet to be definitively elucidated. However, anti-phospholipid antibodies and elevated D-dimer are present in many patients who develop thromboembolism. In addition, chronic upregulation and exhaustion of the immune system may lead to a pro-inflammatory and hypercoagulable state, increasing the likelihood for induction of thromboembolism or stroke. This article provides an up-to-date review on the proposed etiologies for thromboembolism and stroke in patients with long-COVID-19 and to assist health care providers in examining patients who may be at a higher risk for developing these pathologies.